Assessing Implementation of Helping Babies Breathe Program Through Observing Immediate Care of Neonates at Time of Delivery - Mayer, Martha; Xhinti, Nomvuyo; Dyavuza, Vuyiswa; Bobotyana, Luzuko; Perlman, Jeffrey; Velaphi, Sithembiso (Frontiers in Pediatrics, 2022)
Background: Training in neonatal resuscitation has been shown to reduce deaths related to intrapartum asphyxia. Helping Babies Breathe (HBB) is a simulation-based program focusing on training healthcare providers (HCP) in immediate neonatal care including stimulation, initiating bag mask ventilation (BMV) in the absence of breathing by one minute of life, and delayed (30-60 seconds after birth) umbilical cord clamping (DCC). Data on implementation of HBB post-training are limited. Objectives: To determine time from birth to spontaneous breathing, cord clamping and initiation of BMV in a setting where the majority of HCP are HBB trained Methods: Two research nurses observed deliveries conducted in two referral hospitals. Timing included the onset of breathing, cord clamping and initiation of BMV. Deliveries were grouped according to mode of delivery. Results: 496 neonates were observed; 410 (82.7%) cried or had spontaneous breathing (median time 17 seconds) soon after birth, 25/86 (29%) of those not breathing responded to stimulation, 61 (12.3%) required BMV and 2 (0.4%) required chest compression and/or adrenalin. Neonates delivered by caesarean section (CS) took longer to initiate first breath than those delivered vaginally (median time 19 vs 14 seconds; p=0.009). Complete data was available in 58/61 (95%) neonates receiving BMV, which was initiated in 54/58 (93%) cases within 60 seconds of life (the “Golden Minute”). Median time to cord clamping was 74 seconds; with 414 (83.5%) and 313 (63.0%) having cord clamped at ≥30 and ≥60 seconds respectively. Factors associated with BMV were CS delivery (odds ratio (OR) 29.9; 95% confidence interval (CI) 3.37-229), low birth weight (LBW) (birthweight <2500 grams) (OR 2.47; 95%CI 1.93-5.91) and 1 minute Apgar score < 7 (OR 149; 95%CI 49.3-5021). DCC (≥60sec) was less likely following CS delivery (OR 0.14; 95% CI 0.02-0.99) and being LBW (OR 0.43; 95%CI 0.24-0.77). Conclusion: Approximately 83% of neonates initiated spontaneous breathing soon after birth and 29% of those not breathing responded to physical stimulation. BMV was initiated within the Golden Minute in most neonates, but under two-thirds had DCC (≥60 sec). HBB implementation followed guidelines, suggesting that knowledge and skills taught from HBB are retained and applied by HCP.